2021
DOI: 10.1126/science.abe4629
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Global distribution of earthworm diversity”

Abstract: Phillips et al. (Reports, 25 October 2019, p. 480) incorrectly conclude that tropical earthworm communities are less diverse and abundant than temperate communities. This result is an artifact generated by some low-quality datasets, lower sampling intensity in the tropics, different patterns in richness-area relationships, the occurrence of invasive species in managed soils, and a focus on local rather than regional richness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…It is important to mention that astomes isolated from African glossoscolecids and megascolecids exhibit a very different diversification mode in which duplications overdominate (Figure 4C). Such contrasting diversification patterns between European and African astomes might be ascribed to the different ranges of their hosts, which very likely follow the Rapoport rule (James et al, 2021). Earthworm ranges are narrower in low latitudes, which in turn decreases the chance for host switching after duplication.…”
Section: Coevolution Of Astomes With Their Earthworm Hostsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to mention that astomes isolated from African glossoscolecids and megascolecids exhibit a very different diversification mode in which duplications overdominate (Figure 4C). Such contrasting diversification patterns between European and African astomes might be ascribed to the different ranges of their hosts, which very likely follow the Rapoport rule (James et al, 2021). Earthworm ranges are narrower in low latitudes, which in turn decreases the chance for host switching after duplication.…”
Section: Coevolution Of Astomes With Their Earthworm Hostsmentioning
confidence: 99%
“…Since astomes are intimately connected with their earthworm hosts and adapted to the particular physicochemical conditions of their digestive tract (Nana et al, 2012(Nana et al, , 2014, it might be assumed that the evolution and distribution of astomes have been significantly shaped by the diversification of their earthworm hosts. James et al (2021) suggested that the distribution of earthworms follows the Rapoport rule, which says that species latitudinal ranges are narrower in low latitudes than in high latitudes (Stevens, 1989). Interestingly, Benovics et al (2018) proposed that the diversity of symbionts associated with hosts having small distribution areas is lower compared with the diversity of symbionts whose hosts exhibit a large distribution area.…”
Section: Introductionmentioning
confidence: 99%
“…The global distribution of soil fauna and their consumption of litter is interpreted to depend on a set of hierarchical factors like climate, soil properties, and vegetation, which are often themselves interrelated 19 , 24 , 28 , 42 . Climate modifies litter decomposition indirectly via its effects on vegetation, soil type, and soil organismic communities 19 , 28 , 43 , 44 . For example, a global study by Wall et al 19 reported that soil animals increased decomposition rates in temperate and wet tropical climates but exerted neutral effects where temperature or moisture constrain biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of lumbricid earthworms has been largely driven by paleoclimatic and paleogeographic events (e.g., Pérez-Losada et al, 2011 ; Fernández et al, 2013 ; Domínguez et al, 2015 ; James et al, 2021 ). Central Europe is the ancestral area for a large portion of known lumbricid genera, whose diversification was very likely shaped by range expansion and retraction due to global climatic changes from the Paleocene–Eocene epochs to the Pleistocene ( Marchán et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%